Wind energy in Brazil: an overview and perspectives under the triple bottom line. Issue 2 (2nd March 2019) - Lucena, Juliana de Almeida Yanaguizawa; Lucena, Klayton Ângelo Azevedo
Abstract: In recent years, Brazilian wind energy has been growing on a fast trajectory, with the prospect of being the second main source of energy in the year 2019 after hydroelectricity. It should be reaching an installed capacity of more than 20 GW by 2022. In this context, this work presents the evolution and the current scenario of wind energy in Brazil, bringing a discussion on the issues surrounding wind energy and the environmental, social and economic pillars of the sustainability. This study highlights the Northeast region because it has more than 85% of the wind capacity in the country and, at the same time, it contains the cities with the lowest human development indexes. Rotor-blade manufacturing methods and composite materials recycling after the turbine lifetime are considered. Construction, operation and maintenance aspects of wind turbines are also discussed. Wind-energy concepts are described from a bibliographic survey and previous experiences of the authors.